2020
DOI: 10.1055/a-1204-5116
|View full text |Cite
|
Sign up to set email alerts
|

Die Nutzung von sozialen Medien durch Kinder und Jugendliche

Abstract: ZUSAMMENFASSUNGIm Jahr 2020 stellt die gewohnheitsmäßige Nutzung des Internets gerade unter Kindern und Jugendlichen ein selbstverständliches Freizeitverhalten dar. In dieser Altersgruppe sind es überwiegend Online-Computerspiele, zunehmend aber auch soziale Medien, die sich größter Beliebtheit erfreuen. Neben den unbestrittenen Vorteilen, die insbesondere soziale Medien bieten, verdeutlicht ein Blick auf verfügbare Forschungsbefunde, dass gerade bei einem übermäßigen Gebrauch durchaus auch von negativen Effek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…This finding confirms the assumption that social networking and playing computer games have a particularly addictive potential, e.g., because these activities strongly hook children's and adolescents' attention and increase the psychophysiological state of arousal, e.g. due to the pleasure of playing or constant social comparisons with others [ 14 , 40 , 41 ]. The findings showed that among children and adolescents, the amount of PSU symptoms increases with age.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding confirms the assumption that social networking and playing computer games have a particularly addictive potential, e.g., because these activities strongly hook children's and adolescents' attention and increase the psychophysiological state of arousal, e.g. due to the pleasure of playing or constant social comparisons with others [ 14 , 40 , 41 ]. The findings showed that among children and adolescents, the amount of PSU symptoms increases with age.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, we explored whether long smartphone usage times and specific smartphone usage patterns (e.g., intensive social networking or intensive gaming) are associated with PSU symptoms. Based on previous studies [ 12 , 13 ], we expected significant associations with long usage times and, in particular, with intensive social networking [ 40 , 41 ]. Another aim was to investigate associations between PSU symptoms and long smartphone usage times (on the one hand) and socio-demographic factors such as age, sex, and SES (on the other hand).…”
Section: Introductionmentioning
confidence: 99%
“…Reinecke et al (2017) assume that besides the aspects that were just mentioned there are also motivational factors, such as social pressure and the fear of missing out, that might lead to a problematic usage of social media and thus to digital stress which might manifest in symptoms of burn-out, anxiety disorders, sleeping disorders, depression, inner restlessness, and lack of drive. In this context, the psychological concept of FoMo (Fear of Missing out) is important; it describes the fear of missing out on special events in a social community, of losing popularity, and of getting socially excluded if one does not fully dedicate to the respective community (Müller, 2020). Resulting from this, the people affected develop the need of being constantly informed about what other people do and experience.…”
Section: Fomo-fear Of Missing Outmentioning
confidence: 99%
“…There is no doubt that digitalization and the establishment of social media in everyday life as a consequence thereof have provoked a change in the German society (Buttkewitz, 2020). Some refer to it as revolution of social communication (Leiner, 2012) whereas others regard this change in the creation of interpersonal relationships as digital stress (Müller, 2020). Even though the use of social media is mainly determined by the social needs and motifs of the single users, it is still doubtful if social networks can meet those needs or if they even constitute a risk to the users' mental health (Riehm et al, 2019;Kreutzer, 2020).…”
Section: Impact Of the Use Of Digital Media On Mental Healthmentioning
confidence: 99%
“…Fomo-Fear of missing out Reinecke et al (2017) assume that besides the aspects that were just mentioned there are also motivational factors, such as social pressure and the fear of missing out, that might lead to a problematic usage of social media and thus to digital stress which might manifest in symptoms of burn-out, anxiety disorders, sleeping disorders, depression, inner restlessness, and lack of drive. In this context, the psychological concept of FoMo (Fear of Missing out) is important; it describes the fear of missing out on special events in a social community, of losing popularity, and of getting socially excluded if one does not fully dedicate to the respective community (Müller, 2020). Resulting from this, the people affected develop the need of being constantly informed about what other people do and experience.…”
Section: Social Media Addictionmentioning
confidence: 99%